Online learning implementation in the faculty of social sciences during the covid-19 pandemic - Dyah Kumalasari; Suhadi Purwantara; Suranto Aw; Supardi Supardi; Grendi Hendrastomo (Journal of Social Studies (JSS), 2022)
The COVID-19 pandemic has revolutionized the field of education. Online learning is the right solution to replace in-person learning. Improvement and development of the online learning process are really needed to provide a meaningful learning experience for students. This study aimed to examine the implementation of online learning in the Faculty of Social Sciences, Universitas Negeri Yogyakarta/FIS UNY during the pandemic. The quantitative observational approach with a cross-sectional survey was employed with the qualitative method done in group discussions. The respondents were selected using proportional stratified random sampling on all study programs in FIS UNY. Data were collected through an online survey and limited interviews to investigate students’ and lecturers’ experiences of online learning more deeply. In FIS UNY, online learning was mostly conducted through online synchronous learning. Besides, online learning was done using a learning management system developed by the university (BeSmart). There were several factors that influenced the practice of online learning at the faculty, namely the availability of learning devices, speed and stability of internet connection, and conducive learning environment. As many as 25.6% of students had issues related to learning devices. Then, 66.9% of the students stated that they did not have a stable internet connection which caused problems during the learning process. At last, 62.79% of the students admitted that it was difficult to focus on the learning process because their learning environment was not conducive. Besides IT skills, students’ independence and learning motivation were the internal factors influencing the online learning process. Another issue related to online learning was the lack of responses and feedback from the lecturers on the activities done by the students.